2012
DOI: 10.1093/annonc/mds044
|View full text |Cite
|
Sign up to set email alerts
|

78O_PR The Role of Ap-1 in Endocrine-Resistant Breast Cancer

Abstract: Endocrine resistance is a major clinical issue. AP-1 is a transcription factor downstream of different growth factor receptors (GFR) and stress-related signaling cascades implicated in endocrine resistance. We have previously shown that acquired endocrine resistance is associated with increased AP-1 activity. Moreover, AP-1 modulates the estrogen receptor (ER) transcriptional program, especially upon high GFR signaling. We therefore hypothesized that interfering with AP-1 could circumvent endocrine resistance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Inhibition of the transcription factor activator protein 1 potentiates the effect of endocrine treatment and circumvents endocrine resistance L. Malorni (Oncology, Hospital of Prato, Prato, Italy) and colleagues have previously shown that acquired endocrine resistance is associated with increased activator protein 1 [AP-1, a transcription factor downstream of different growth factor receptors (GFRs)] activity and that AP-1 modulates the ER transcriptional programme, especially with high GFR signalling [Malorni et al 2012]. Thus, AP-1 modulation may circumvent endocrine resistance.…”
Section: Molecular Biologymentioning
confidence: 99%
“…Inhibition of the transcription factor activator protein 1 potentiates the effect of endocrine treatment and circumvents endocrine resistance L. Malorni (Oncology, Hospital of Prato, Prato, Italy) and colleagues have previously shown that acquired endocrine resistance is associated with increased activator protein 1 [AP-1, a transcription factor downstream of different growth factor receptors (GFRs)] activity and that AP-1 modulates the ER transcriptional programme, especially with high GFR signalling [Malorni et al 2012]. Thus, AP-1 modulation may circumvent endocrine resistance.…”
Section: Molecular Biologymentioning
confidence: 99%